A CRITIQUE OF CLASSICAL CONDITIONS OF KNOWLEDGE AND IMPLICATION ON NIGERIAN EDUCATION - Kani, Umar Mohammed; Muhammad, Auwal (Sokoto Educational Review, 2021)
This paper appraised the three classical conditions of knowledge and their implications on Nigerian education. The conditions were drawn from Platos’s formula of knowledge episteme as “justified true belief” in theaetetus, later itemised and critiqued as belief, evidence and truth by epistemologists. The knowledge in question is a propositional type that deals with the state of affairs mostly in the professional realm, on the creed that knowledge is possible. Belief is a subjective criterion with uncertainty issues, evidence seems objective requirement but has adequacy and construal questions, also the truth that appears to be an objective condition has relativism-absolutism and necessity-contingency disputes in addition to dependency weakness. However, Nigeria's educational process requires the intervention of the conditions for genuine knowledge, which implicate functionalism, scientism, pragmatism, progressivism, learner-centredness, meaningful learning, liberality, democracy, adequacy and relevancy of instructional facilities, ideal class size and intrinsic motivation.